Centros de referência: Precisam-se? - Clode,Nuno (2018)
Referral Centers for particular situations are necessary and an added value for Nacional Obstetrics. Centers for fetal therapy and for management of placenta accreta spectrum disorders are a good example of this need. Creating teams with experience is the only way to answer to the challenges that Modern Obstetrics poses to us.